Empowerment through Hindu nationalism? - Deshpande, C (2005)
﻿ This dissertation explores whether women and men can be empowered through cultural nationalism based on religious/ethnic identities. Religious fundamentalism is typically not associated with women's empowerment. As a patriarchal, Hindu nationalist party that advocates violence, the Shiv Sena is also an unlikely agent of women's empowerment. Yet, the Sena has been attracting numerous women who claim to have gained confidence through the party. Using the Shiv Sena as my case study, I interviewed four male and seven female Shiv Sena members using the biographic narrative method. By examining their biographic narratives and interviews of their families and colleagues, I was able to delineate the different empowerment cycles for men and women in Shiv Sena and determine each participant's level of empowerment. The empowerment framework defined by Jo Rowlands (1997), which distinguishes between personal, collective, and relational empowerment, serves as the basis of my assessment of women's and men's empowerment. As violence is generally disregarded as a means of empowerment, I discuss it in relation to the construction of empowering cultural identities. While establishing theoretical frameworks regarding empowerment, cultural identity and gender, I also examine the disempowerment of Maharashtrians (whom Shiv Sena originally represented) by the socio-economic and historical conditions of Bombay, India. I then demonstrate how Shiv Sena, led by its Chief, Bal Thackeray, has constructed a new hegemonic masculine identity for Maharasthrian men as a means of empowerment. In the final chapters, I examine Shiv Sena's impact on the lives of individual women and men. This analysis revealed that despite the patriarchal constraints imposed by the Sena, women were becoming personally empowered in both the private and public spheres. In contrast, while Shiv Sena men were achieving collective empowerment in the public sphere, they had more difficulty becoming personally empowered in both the home and workplace.